Influence of Paddy Straw of Different Particle Sizes in the Diet on Nutrient Utilisation and Enteric Methane Emissions in Murrah Buffalo Calves - Budhani, Lalit; Mohini, Madhu; Datt, Chander; Thakur, S. S. (Indian Journal of Animal Nutrition, 2018)
Fifteen Murrah male calves were divided into three groups of five each. All the animals were offered a diet consisting of paddy straw, concentrate mixture and berseem (Trifolium alexandrinum) fodder ad lib. in 50: 40: 10 ratio. Group G-I was fed with paddy straw of small particle size (0.88 cm), G-II with long particle size (2.45 cm) and G-III with unchaffed paddy straw. The feed intake was higher (P<0.05) in chaffed paddy straw fed group (G-I and G-II) than unchaffed paddy straw fed group (G-III). The digestibility coefficients of DM, OM and ADF were significantly (P<0.05) higher in group G-II as compared to groups G-I and G-III. The digestibility of NDF was higher (P<0.05) in groups G-I compared to G-II and G-III. The digestibility of CP and EE was similar in all the groups. Methane production (g/kg DMI or g/kg DDMI or % of GE, DE and ME) was lower (P<0.05) in groups G-I and G-II as compared to group G-III. Thus, the inclusion of chaffed paddy straw of medium size particles (2-3 cm) in the rations of growing buffalo calves improved (P<0.05) the voluntary feed intake and reduced enteric methane emissions.